2017
DOI: 10.21511/imfi.14(1).2017.14
|View full text |Cite
|
Sign up to set email alerts
|

Islamic finance: more expectations and less disappointment

Abstract: Islamic finance has faced a two-fold criticism from scholars; viz. constructive criticism and destructive criticism. Majority of the scholars criticize it with the intention to improve its overall development, but some scholars are more negative in their criticism. This paper proposes that Islamic banks (a component of Islamic finance) are not charitable institutions, but are the intermediary institutions that take care of investors’ expectations to keep the time value and return to their investments intact wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…Kamarulzaman and Madun (2013) found that the frontline employees in IFIs themselves are unaware and unclear on their own products/services, which finally fail them to market their products/services to the customers. Lone and Ahmad (2017) argued that IFIs are incapable of understanding the needs of the customer, which finally fails them to train their employees and tailor their product. The significance of human resources in the takaful industry has been studied by a number of researchers such as Salleh et al (2012) on the Quranic conditions applicable to the agents in takaful; Zawawi et al (2021) on takaful practitioners' sustainable practice; Njagi (2019) on personality traits of takaful salesforce; and Ghani and Shaari (2016) on ethical aspects of takaful agents.…”
Section: Review Of Literature and Theoretical Underpinningmentioning
confidence: 99%
“…Kamarulzaman and Madun (2013) found that the frontline employees in IFIs themselves are unaware and unclear on their own products/services, which finally fail them to market their products/services to the customers. Lone and Ahmad (2017) argued that IFIs are incapable of understanding the needs of the customer, which finally fails them to train their employees and tailor their product. The significance of human resources in the takaful industry has been studied by a number of researchers such as Salleh et al (2012) on the Quranic conditions applicable to the agents in takaful; Zawawi et al (2021) on takaful practitioners' sustainable practice; Njagi (2019) on personality traits of takaful salesforce; and Ghani and Shaari (2016) on ethical aspects of takaful agents.…”
Section: Review Of Literature and Theoretical Underpinningmentioning
confidence: 99%
“…Source: tracking results, processed While, assets-based provinces in Indonesia can be seen in the following table : Table -2 Source: tracking results, processed However, on the other hand, people's expectations (Lone & Ahmad, 2017) of the vital role of Islamic banking (Yuniarti, 2017) in order to participate in helping the growth as well as the development of the level of welfare of the Indonesian people (Saputro et al, 2018). Until now, it assessed by many Islamic banking experts or Islamic economics themselves are still far from expectations, even blunt, given the banking behavior that it runs not much different from conventional banking (Elsa et al, 2018(Elsa et al, , pp.…”
Section: Table-1 Sharia Banking Growthmentioning
confidence: 99%
“…While there are limitations in existing financial sector performance evaluation systems as far as the IBSI is concerned, the literature depicts many expectations from the industry (Lone & Ahmad, 2017). At times those mounting expectations are beyond the capacity and mandate of the IBSI.…”
Section: Introductionmentioning
confidence: 99%